1909 N.C. Sess. Laws 777-78 - (:unkn) unknown (My University, 1909)
Priv. Laws, ch. 345, § 23, pt. 14: [O]n dealers in pistols, guns, dirks, bowie knives, sling shots, brass or metal knuckles or other like deadly weapons, in addition to all other taxes, a license tax not exceeding fifty dollars; on dealers in firecrackers, Roman candles, skyrockets, toy pistols or fireworks of any kind, a tax not exceeding fifty dollars.
Keywords: TAX - DEALERS